THE EFFECT OF INFORMATION TECHNOLOGY MODERATION ON RELATIONSHIP PLANNING, IMPLEMENTATION, REPORTING, BUDGET EVALUATION ON PERFORMANCE ACCOUNTABILITY - Wendra Aliffandi; Hasni Yusrianti; Emylia Yuniarti (I-Finance Journal, 2023)
This study aims to determine the effect of information technology moderation on the relationship between planning, implementation, reporting and evaluation of the budget on performance accountability of the Regional Government of Palembang City. The population in this study were all Regional Apparatus Organizations (OPD) within the scope of Palembang City Government as many as 52 OPD. The sample used the criteria and 3 people were taken from each OPD so that a total of 156. The analysis technique used SEM PLS. The results of the study show that directly only the technology variable that influences performance accountability while the planning, implementation, reporting and evaluation variables do not affect performance accountability. Information technology is only able to moderate the relationship between budget planning and performance accountability variables, while other variables, information technology is not able to moderate it.